Aplikasi Smart Traffic light untuk Monitoring Marka Jalan - Iwan Ady Prabowo, Didik Nugroho, Kustanto (STMIK Sinar Nusantara, 2014)
One important instrument in regulating the traffic is a traffic light. the traffic lights that exist today help smooth and traffic controlBut sometimes the traffic lights into one of the causes accidents and the traffic congestion. This is can be occur because the the traffic lights, at work not to be adaptive and flexible so as to raises many accidents and traffic violations at traffic light.Research the purpose to design a smart traffic light control system. The basis the ideas results of this study created a good system and generate the traffic to adaptively setting that can reduce the number of offense in the traffic lights that improve the efficiency and effectiveness of a traffic light itself. Keyword: lalu lintas, traffic light